2012
DOI: 10.1681/asn.2011070701
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylated IgA Rheumatoid Factor Induces IgA Deposits and Glomerulonephritis

Abstract: Structural aberrations of O-linked glycans present in the IgA1 hinge region are associated with IgA nephropathy, but their contribution to its pathogenesis remains incompletely understood. In this study, mice implanted with hybridoma secreting 6-19 IgA anti-IgG2a rheumatoid factor, but not 46-42 IgA rheumatoid factor bearing the same IgA allotype, developed mesangial deposits consisting of IgA, IgG2a, and C3. Studies in immunoglobulin-and C3-deficient mice revealed that the development of these glomerular lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
(39 reference statements)
0
31
0
Order By: Relevance
“…In a mouse model for IgA nephritis, mice lacking either C3 or IgG did not develop the IgAN phenotype [39]. Also, glomerular MBL deposition has been found to be associated with a severe clinical presentation, and initial C4d deposition has been shown to be a risk factor for a worse clinical outcome [24,40].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…In a mouse model for IgA nephritis, mice lacking either C3 or IgG did not develop the IgAN phenotype [39]. Also, glomerular MBL deposition has been found to be associated with a severe clinical presentation, and initial C4d deposition has been shown to be a risk factor for a worse clinical outcome [24,40].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…10 Indeed, we recently demonstrated the presence of O-glycans in the hinge region of murine IgA monoclonal rheumatoid factors (RFs) bearing the Igh-2 a allotype. 11 More significantly, comparative analysis of two murine IgA anti-IgG2a RFs bearing the Igh-2 a allotype (6-19 and 46-42) revealed that highly O-glycosylated 6-19 IgA RF mAbs induced severe glomerular lesions characterized by abundant mesangial IgA deposits, together with IgG2a and C3, whereas poorly O-glycosylated 46-42 IgA failed to provoke glomerular lesions. However, we also noted a marked difference in the structure of N-linked glycans (N-glycans) present in the CH1 domain between nephritogenic 6-19 IgA RF and non-nephritogenic 46-42 IgA RF (i.e., biantennary and triantennary complex types in [6][7][8][9][10][11][12][13][14][15][16][17][18][19] IgA versus hybrid type with features of both high mannose-type and complex-type oligosaccharides in 46-42 IgA).…”
mentioning
confidence: 97%
“…However, we also noted a marked difference in the structure of N-linked glycans (N-glycans) present in the CH1 domain between nephritogenic 6-19 IgA RF and non-nephritogenic 46-42 IgA RF (i.e., biantennary and triantennary complex types in [6][7][8][9][10][11][12][13][14][15][16][17][18][19] IgA versus hybrid type with features of both high mannose-type and complex-type oligosaccharides in 46-42 IgA). Thus, we could not exclude the implication of structural differences in N-glycans in IgAN-like glomerular lesions induced by [6][7][8][9][10][11][12][13][14][15][16][17][18][19] IgA RF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of JASN, Otani et al 1 describe an interesting murine model for studies of IgA-associated GN. The authors explore the nephritogenic potential of two different monoclonal IgA rheumatoid factors (designated as [6][7][8][9][10][11][12][13][14][15][16][17][18][19] IgA and 46-42 IgA) specific for murine IgG2a in relation to potential differences in glycosylation of these IgA antibodies.…”
mentioning
confidence: 99%